Development of Powtoon-Assisted Animation Video for Poetry Writing Material in Grade VIII at SMPN 1 Sitiung - Salahuddin, Amar; Marlianda, Rendi; Yani, Rahma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop a learning media using Powtoon-assisted animation videos for teaching poetry writing. The researcher chose the CapCut application because it is accessible and easy to use for creating learning videos that actively engage students' visual and auditory senses, enhancing the absorption of the material. This research employed a Research and Development (R&D) method using the 4D model, which consists of the stages: define, design, develop, and disseminate. The study was conducted at SMPN 1 Sitiung in the 2025/2026 academic year, with 29 grade VIII students as participants. Data collection techniques included questionnaires for student responses, teacher responses, media expert validation sheets, material expert validation sheets, and language expert validation sheets. The results show that the researcher successfully developed a learning video as a teaching aid for reading poetry texts. The video was considered valid based on expert validations: media expert validation scored 100%, categorized as